Transformative Paleobotany 2018
DOI: 10.1016/b978-0-12-813012-4.00022-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Convergence in Forest Microfungi Provides a Proxy for Paleogene Forest Structure

Abstract: Amber, fossilized plant resin from gymnosperms and angiosperms, is renowned for preserving a wide range of organisms in microscopic fidelity. These so-called amber inclusions comprise many groups of organisms, ranging frombacteria to arthropods and vertebrates (Penney, 2010; Ragazzi and Schmidt, 2011;Grimaldi and Ross, 2017). Organisms trapped in amber typically derive from forest ecosystems where they became stuck to resin outpourings in their habitats (Seyfullah and Schmidt, 2015). In addition, ambers are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 133 publications
1
11
0
Order By: Relevance
“…Our study suggests that the diversity of ferns in the Baltic amber forest was low and that at least epiphytic and climbing ferns were rare or even absent. This is generally in line with a recently suggested temperate origin of Baltic amber (Kaasalainen et al, ; Sadowski et al, ; Rikkinen & Schmidt, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study suggests that the diversity of ferns in the Baltic amber forest was low and that at least epiphytic and climbing ferns were rare or even absent. This is generally in line with a recently suggested temperate origin of Baltic amber (Kaasalainen et al, ; Sadowski et al, ; Rikkinen & Schmidt, ).…”
Section: Discussionsupporting
confidence: 91%
“…Following the latest reconstruction of the Baltic amber forest, it was a heterogeneous landscape with coastal swamps, bogs, lowland swamps, riparian forests, and mixed conifer‐angiosperm forest, intermingled by drier and light open patches (Sadowski et al, , , , ). The climate was most likely warm‐temperate to temperate and relatively humid (Kaasalainen et al, ; Sadowski et al, ; Rikkinen & Schmidt, ), so generally favoring terrestrial ferns but not epiphytic nor climbing ferns.…”
Section: Discussionmentioning
confidence: 99%
“…Woodpecker-mediated dispersal could be especially important for rare and highly substrate-specific species, such as certain calicioid lichens (Rikkinen & Schmidt, 2018;Tibell, 1994) or aspen specialists (Gjerde et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sorocybe resinae ( Chaetothyriales, Herpotrichiellaceae ) and its synasexual morph Hormodendrum resinae ( Seifert et al 2007 ), and S. oblongispora ( Crous et al 2019 ), represent asexual Eurotiomycetes that are also often found on resin. The association of these fungi with conifer resin has existed for at least 35 M years as evidenced by fossilized specimens in Palaeogene amber ( Rikkinen & Poinar 2000 , Tuovila et al 2013 , Beimforde et al 2014 , Rikkinen & Schmidt 2018 ). While other resinicolous fungi have not received as much recent attention, a significant number occurs in other classes.…”
Section: Introductionmentioning
confidence: 99%